(untitled) (Perner’s Contacts, 2010)
This paper examines the modelling of the traffic impact on the planned express road R3 on the transport network of the city of Martin. It proved that the modelling issue can be very useful tool for evaluation of planning the building the new road infrastructure, especially in area where are presented the problems with traffic volume.